Occupational ergonomics and health. - Ong, Choon-Nam (1992)
Points out that recent studies have suggested that many occupational diseases are connected to poor design of tools, machines and workplace. Stresses that the correct matching of man, technology, task and organization to form a total entity capable of higher job performance is now an important function of management, and the ergonomic approach can go a long way to help meet this objective.